Peranan Perpustakaan Penjara dalam pembentukan sahsiah pesalah juvana - Rafedzi, Ezza Rafedziawati Kamal; Abdullah, Abrizah; Yu, Halida (Persatuan Pustakawan Malaysia, 2015)
The increasing crime rate among teenagers currently is worrying. It seems to be the current trend that has to be followed by teenagers. The mistakes that drive them to criminal acts resulting in their imprisonment is harmful to teenagers since they have to be kept behind bars while other teenagers are either studying or job hunting. This article focuses on the effectiveness of prison libraries in forming the character of juvenile criminals while they are in prison. Besides getting religious education/advice and behaviour therapy, preparatory rehabilitation programmes should be based on educational and skills programmes which are closely related to usage of the prison libraries. The rehabilitation process for juvenile offenders is important because without suitable rehabilitation, juvenile offenders will always be dissatisfied, restless and can easily behave violently. Prison libraries have a major role in the rehabilition process and character formation of these juvenile offenders through the provision of reading materials that have positive values.